Mediterranean diet and Alzheimer disease mortality. - Scarmeas, Nikolaos; Luchsinger, Jose A; Mayeux, Richard; Stern, Yaakov (Neurology, 2007)
BACKGROUND: We previously reported that the Mediterranean diet (MeDi) is related to lower risk for Alzheimer disease (AD). Whether MeDi is associated with subsequent AD course and outcomes has not been investigated. OBJECTIVES: To examine the association between MeDi and mortality in patients with AD. METHODS: A total of 192 community-based individuals in New York who were diagnosed with AD were prospectively followed every 1.5 years. Adherence to the MeDi (0- to 9-point scale with higher scores indicating higher adherence) was the main predictor of mortality in Cox models that were adjusted for period of recruitment, age, gender, ethnicity, education, APOE genotype, caloric intake, smoking, and body mass index. RESULTS: Eighty-five patients with AD (44%) died during the course of 4.4 (+/-3.6, 0.2 to 13.6) years of follow-up. In unadjusted models, higher adherence to MeDi was associated with lower mortality risk (for each additional MeDi point hazard ratio 0.79; 95% CI 0.69 to 0.91; p = 0.001). This result remained significant after controlling for all covariates (0.76; 0.65 to 0.89; p = 0.001). In adjusted models, as compared with AD patients at the lowest MeDi adherence tertile, those at the middle tertile had lower mortality risk (0.65; 0.38 to 1.09; 1.33 years' longer survival), whereas subjects at the highest tertile had an even lower risk (0.27; 0.10 to 0.69; 3.91 years' longer survival; p for trend = 0.003). CONCLUSION: Adherence to the Mediterranean diet (MeDi) may affect not only risk for Alzheimer disease (AD) but also subsequent disease course: Higher adherence to the MeDi is associated with lower mortality in AD. The gradual reduction in mortality risk for higher MeDi adherence tertiles suggests a possible dose-response effect.
Keywords: Age Distribution; Aged; Aged, 80 and over; Alzheimer Disease; Apolipoproteins E; Body Mass Index; Brain; Cohort Studies; Diet, Mediterranean; Energy Intake; Female; Follow-Up Studies; Humans; Male; New York; Patient Compliance; Prospective Studies; Risk Factors; Sex Distribution; Smoking; Survival Rate